Glacier tourism without ice: Envisioning future adaptations in a melting world - Salim, Emmanuel (Frontiers in Human Dynamics, 2023)
Climate change is causing profound changes in high mountain environments, including the rapid retreat of glaciers. The retreat and potential disappearance of Alpine glaciers during the 21st century raises questions about the future of glacier tourism sites. This perspective article reflects on these changes with a desk-based approach to suggest three possible ways glacier tourism can adapt to anticipated glacier loss. These three strategies include further developing geotourism, transforming last-chance tourism into ‘dark tourism’, and using virtual reality to ‘virtually’ reconstruct disappearing glaciers. This paper draws on three cases to discuss the potential of these strategies. The first is the Aletsch Glacier, the largest in the Alps, which is listed as a UNESCO World Heritage Site. It has also been the subject of recent work on geotourism. The second case is Mer de Glace, the largest glacier at the Montenvers site in France. This glacier has been studied in the context of last-chance tourism. The final case is the Mortaretsch Glacier in Switzerland, which can be reached from Diavolezza and has not been the subject of many studies. However, this site is one of the first to incorporate virtual reality technology into the tourist experience of the glacier.